2021
DOI: 10.3390/molecules26216654
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Identification of NADPH Cytochrome P450 Reductase from Panax ginseng

Abstract: Ginseng (Panax ginseng C.A. Mey.) is a precious Chinese traditional medicine, for which ginsenosides are the most important medicinal ingredients. Cytochrome P450 enzymes (CYP450) and their primary redox molecular companion NADPH cytochrome P450 reductase (CPR) play a key role in ginsenoside biosynthesis pathway. However, systematic studies of CPR genes in ginseng have not been reported. Numerous studies on ginsenoside synthesis biology still use Arabidopsis CPR (AtCPR1) as a reductase. In this study, we isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In order to improve the ginsenoside content of P. ginseng , several genes from different gene families capable of affecting the synthesis of ginsenosides were identified and analyzed, such as, bHLHs [ 36 ], bZIPs [ 37 ], P450s [ 38 ], GRASs [ 39 ], and MYBs [ 40 ]. With the development of synthetic biology, the heterologous synthesis of ginsenosides in microbial cell factories offers a sustainable solution [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the ginsenoside content of P. ginseng , several genes from different gene families capable of affecting the synthesis of ginsenosides were identified and analyzed, such as, bHLHs [ 36 ], bZIPs [ 37 ], P450s [ 38 ], GRASs [ 39 ], and MYBs [ 40 ]. With the development of synthetic biology, the heterologous synthesis of ginsenosides in microbial cell factories offers a sustainable solution [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both CPR classes were reported to be able to support the in vitro activities of CYPs involved in specialized metabolism ( Rana et al., 2013 ). However, based on numerous functional analyses in planta , CPR class I was believed to be responsible for basal or constitutive metabolisms, while CPR class II was more responsible for adaptation and defense mechanisms, involving numerous specialized metabolisms ( Rana et al., 2013 ; Parage et al., 2016 ; Huang et al., 2021 ; Zou et al., 2021 ). This study showed that LjCPR1 is closely involved with CYP716A51, a C-28 oxidase, which is involved in triterpenoid biosynthesis, one of the specialized metabolisms in L. japonicus .…”
Section: Discussionmentioning
confidence: 99%
“…CPR class I is reported to be constitutively expressed and plays a role in primary or basal constitutive metabolism, while CPR class II is inducible by environmental stimuli and is involved in defense mechanisms through plant secondary metabolism ( Parage et al., 2016 ). Different tissue expression profiles of CPR classes I and II were reported in Withania somnifera ( Rana et al., 2013 ), Panax ginseng ( Zou et al., 2021 ), Camellia sinensis ( Huang et al., 2021 ), and Catharanthus roseus ( Parage et al., 2016 ). The differences in the protein sequences and expression levels of CPR classes I and II suggest that they have different roles in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many enzymes including nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase, nicotinamide adenine dinucleotide phosphate hydrogen (NADPH)‐cytochrome P450, NAD(P)H:quinone reductase (NQR) and flavodoxin‐like quinone reductase (FQR) are responsible for reduction of quinones in plants. NADH dehydrogenase and NADPH‐cytochrome P450 catalyze reduction of quinones by one‐electron reaction leading to the accumulation of reactive intermediates such as semiquinone (SQ), which passes a single electron to O 2 to form O 2 − and subsequent other ROS (Møller et al., 2021; Zou et al., 2021). Somewhat differently, NAD(P)H‐dependent quinone reductase family such as NQR and FQR catalyzes the transformation of quinone directly to dihydroquinones (DHQs) by carrying out two electrons, thereby decreasing the formation of SQ (Laskowski et al., 2002; Sparla et al., 1999; Wrobel et al., 2002).…”
Section: Introductionmentioning
confidence: 99%